Analisis Strategi Bisnis Ekspor Ikan Hias Air Tawar (Kasus di PT NAE, Jakarta) Aim of Business strategy analysis toward PT NAE on this research is to identify strengthens and weaknesses of internal and extemal factors of the company and recommend alternative strategies to the company as consideration for releasing essential policy related on fresh water ornamental fish business. Based on analysis through input matrix obtained scores above the average of 2,5, those are 2,545 for IFE and 2,651 for - Andy Saputro; Narni FarmayantiFarmayanti; Iis Diatin (Buletin Ekonomi Perikanan, 2007)
Analisis Strategi Bisnis Ekspor Ikan Hias Air Tawar (Kasus di PT NAE, Jakarta) Aim of Business strategy analysis toward PT NAE on this research is to identify strengthens and weaknesses of internal and extemal factors of the company and recommend alternative strategies to the company as consideration for releasing essential policy related on fresh water ornamental fish business. Based on analysis through input matrix obtained scores above the average of 2,5, those are 2,545 for IFE and 2,651 for EFE. The scores show that PT NAE was enabling in using its internal strength and overcome its internal weakness to gain business opportunities and avoid treats. Based on analysis through matching matrix with SWOT, SPACE, IE and Grand Strategy analysis, result as altematives strategy was produced. The altemative strategies are product development and market penetration. Final step is making priority on recent altemative strategy. Based on as PM analysis. product development is being the 1st strategy to be implemented, and market penetration is being the 2nd. General description on implementing product development is to maintain consumer image toward fresh water omamental fish product and hold product quality and service. General description on market penetration is by doing prornotion strategy optimally to preserve rnarket share of company on targeted country.